2016
DOI: 10.15740/has/ajhs/11.1/220-225
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of school going children (7-9 years) in rural area of Bhilwara district (Rajasthan)

Abstract: The present study was conducted with an objective to assess nutritional status of school going children. The study was conducted in village Hurda of Hurdapanchayatsamiti of Bhilwara district of Rajasthan. Total 120 school going children (15 girls and 15 boys from each school) were selected. Nutritional status of the subjects was assessed by using anthropometric measurements (height and weight), clinical assessment and dietary recall method. All respondents were vegetarian. The height and weight of respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Food consumption pattern revealed that the daily mean intake of food groups-cereals, pulses, leafy vegetables, roots and tubers, other vegetables, fruits, milk and milk products, fats and sugar, was found to be lower in percentage than the recommended dietary intake. Similar, the results regarding food intake of children aged 7-9 years in accordance with Sharma and Lakhawat (2016) who also found that the daily mean intake of the food groups was lower than the RDI in the diets of school children of Bhilwara district of Rajasthan. The daily intake of various food groups is displayed in table 5.…”
Section: Overall Food Intakesupporting
confidence: 87%
“…Food consumption pattern revealed that the daily mean intake of food groups-cereals, pulses, leafy vegetables, roots and tubers, other vegetables, fruits, milk and milk products, fats and sugar, was found to be lower in percentage than the recommended dietary intake. Similar, the results regarding food intake of children aged 7-9 years in accordance with Sharma and Lakhawat (2016) who also found that the daily mean intake of the food groups was lower than the RDI in the diets of school children of Bhilwara district of Rajasthan. The daily intake of various food groups is displayed in table 5.…”
Section: Overall Food Intakesupporting
confidence: 87%